Adult subventricular zone neural stem cells as a potential source of dopaminergic replacement neurons - Cave, John; Wang, Meng; Baker, Harriet (Frontiers in Neuroscience, 2014)
Clinical trials engrafting human fetal ventral mesencephalic tissue have demonstrated, in principle, that cell replacement therapy provides substantial long-lasting improvement of motor impairments generated by Parkinson’s Disease. The use of fetal tissue is not practical for widespread clinical implementation of this therapy, but stem cells are a promising alternative source for obtaining replacement cells. The ideal stem cell source has yet to be established and, in this review, we discuss the potential of neural stem cells in the adult subventricular zone as an autologous source of replacement cells. We identify three key challenges for further developing this potential source of replacement cells: 1) improving survival of transplanted cells, 2) suppressing glial progenitor proliferation and survival, and 3) developing methods to efficiently produce dopaminergic neurons. Subventricular neural stem cells naturally produce a dopaminergic interneuron phenotype that has an apparent lack of vulnerability to Parkinson’s Disease-mediated degeneration. We also discuss whether olfactory bulb dopaminergic neurons derived from adult subventricular zone neural stem cells are a suitable source for cell replacement strategies.